KUALITAS PELAYANAN PROGRAM PREDATOR (PEREKAMAN DATA KARTU TANDA PENDUDUK ELEKTRONIK DENGAN SEPEDA MOTOR) PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KLUNGKUNG - Dwija Putra, I Made (CITIZEN CHARTER, 2018)
ABSTRACT Klungkung Regency became the lowest area in the compliance assessment of public services in Bali Province in 2017. Electronic identity card’s data recording is one of public services that the implementation is still not running well. The elderly, disability, and patient are difficult going to office. This was responded to by forming Predator Program (Electronic Identity Card’s Data Recording by Motorcycle) to improve electronic identity card’s service quality in Klungkung Regency. The purpose of this research is to know service quality of Predator Program (Electronic Identity Card’s Data Recording by Motorcycle). This research was conducted using qualitative descriptive method with data collection techniques such as observation, deep interview, and documentation. The result of this research indicate it still found obstacles on managing the service quality of Predator Program (Electronic Identity Card’s Data Recording by Motorcycle) is still not running well. Keywords: Service Quality, Data Recording, Klungkung